Strategy to Improve the Performance of Regional Government-owned BPR and BPRS through Optimal Funding Contributions from Shareholders - Bangbang Purnawan; Zulganef Zulganef (International Journal of Research in Community Services, 2023)
The regional government established rural banks as financial organizations in an effort to offer services in the financial industry. BPR are a way effort for local governments to bring in local revenues. BPR currently only have a limited amount of capital because it comes only from the APBD. on the other hand, BPR are obligated to constantly offer service enhancements in terms of both service quantity and service quality. So that, to enhance the performance of BPR and BPRS, BPR who are unable to achieve the minimum core capital rules should immediately merge with another BPR that can or be bought by a bank with larger resources or shareholders who are contributing at their maximum potential. Based on the aforementioned issues, the purpose of this study is to present an overview of the approach to enhance BPR or BPRS performance and how shareholder ownership impacts BPR/financial BPRS performance.